Issues of the Charter of the Russian Academy of Sciences - E. Z. Bekbaev (Теоретическая и прикладная юриспруденция)
The relevance of the topic stems from the need for legal support for the development of science as a generally recognized tool for the further progress of society. The Charter of the Russian Academy of Sciences is considered as the main document that fixes the legal status of the Academy of Sciences in the current legislation. The charter solves the problem of a comprehensive and systematic consolidation of the legal status of the Academy of Sciences, holistically covers and regulates in interconnection all, without exception, the most important issues of the organization and activities of the Russian Academy of Sciences. The article gives a general description of the Charter, shows the charter goals and objectives, organizational structure and functions of the Russian Academy of Sciences. An analysis of some problematic issues of the Charter of the Russian Academy of Sciences has been carried out. It is concluded that in the Soviet period of the history of the Russian Academy of Sciences, ambiguous events took place that had an impact on the subsequent development of fundamental science in the context of the country’s transition to market relations. An attempt is made to predict the further course of possible events in the legal regulation of fundamental science, the status of the Russian Academy of Sciences. The article is dedicated to the 300th anniversary of the Russian Academy of Sciences.